Oxytocin-induced anxiogenic behavior in juvenile male rats - Minji Jang (Taylor & Francis Group, 2021)
Oxytocin (OT) is considered beneficial to mental health owing to its anxiolytic, prosocial, and anti-stress effects; however, the adverse effects of OT have been controversial, such as its potentially anxiogenic actions. Although OT influences drug abuse and reciprocally affects vulnerability to drug use, the relationship between OT’s anxiogenic working and nicotine preference intake has not been clearly defined. To clarify this issue, the effect of acute peripheral administration of OT on anxiety and nicotine preference was investigated in juvenile male rats. Anxiogenic behaviors were noticeably increased in OT-administrated rats, with an increase in serum corticosterone levels. Moreover, increased anxiety-like behaviors and corticosterone levels were observed in the OT analog carbetocin-injected rats. In the nicotine preference test, the rats’ aversive responses to initial nicotine choice and preference were not significantly different between saline-injected and OT-injected rats. However, when administered with OT, there was a significant negative correlation between anxiety-like behavior and low-dose nicotine consumption. Collectively, these results provide evidence that acute OT exposure could induce anxiogenic behavior with corticosterone augmentation, contributing to the attenuation of nicotine preference. This suggests that both aspects of OT, as well as their benefits and drawbacks, should be considered.